2017
DOI: 10.1002/dneu.22501
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen signaling is necessary for exercise‐mediated enhancement of motoneuron participation in axon regeneration after peripheral nerve injury in mice

Abstract: Thousands of people each year suffer from peripheral nerve injury. Treatment options are limited, and recovery is often incomplete. Treadmill exercise can enhance nerve regeneration; however, this appears to occur in a sex-dependent manner. Females respond best to short duration, high speed interval training; whereas, males respond best to slower, continuous training. Previous studies have shown a role for testosterone in this process, but the role of estrogen is unknown. To evaluate the role of estrogen signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The local administration of IGF-1 improves the recovery of facial nerve function after a crush injury [ 128 ]. Furthermore, gonadal hormones [ 129 ], like estradiol [ 130 ] and testosterone [ 131 ] contribute increasing axon regeneration after peripheral nerve section. Tuffaha et al [ 132 ] demonstrated that during GH therapy in mice, the peripheral nerve injury accelerates axonal regeneration and myelination, reduces muscle atrophy, and enhances muscle reinnervation.…”
Section: Resultsmentioning
confidence: 99%
“…The local administration of IGF-1 improves the recovery of facial nerve function after a crush injury [ 128 ]. Furthermore, gonadal hormones [ 129 ], like estradiol [ 130 ] and testosterone [ 131 ] contribute increasing axon regeneration after peripheral nerve section. Tuffaha et al [ 132 ] demonstrated that during GH therapy in mice, the peripheral nerve injury accelerates axonal regeneration and myelination, reduces muscle atrophy, and enhances muscle reinnervation.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, reduced Shh signaling was shown to disturb axon regeneration via misregulated myelin degradation 56 . Estrogen signaling has also been implicated in axon regeneration by accelerating peripheral nerve regeneration and increasing motoneuron participation 57,58 . Another unexpected pathway enriched within the AXONO module was Pathogenic Escherichia Coli infection.…”
Section: Discussionmentioning
confidence: 99%
“…3). Thus, estradiol enhances axonal regeneration in peripheral nerves (Acosta et al, 2017) and decreases motoneuron axonal loss and promotes motoneuron dendritic growth in the central nervous system in animal models of spinal cord injury (Sengelaub and Xu, 2018). Estradiol also decreases axonal loss in experimental autoimmune encephalomyelitis in rats.…”
Section: Neuritogenesis Synaptogenesis and Neuronal Plasticitymentioning
confidence: 99%